Current trends in regenerative liver surgery: Novel clinical strategies and experimental approaches - Heil, Jan; Schiesser, Marc; Schadde, Erik (Frontiers in Surgery, 2022)
Liver resections are performed to cure patients with hepatobiliary malignancies and metastases to the liver. However, only a small proportion of patients is resectable, largely because only up to be 70% of liver tissue is expendable in a resection. If larger resections are performed, there is a risk of posthepatectomy liver failure. Regenerative liver surgery addresses this limitation by increasing the future liver remnant to an appropriate size before resection. Since the 1980ies, it has evolved from portal vein embolization (PVE) to a dizzying multiplicity of methods that is hard to keep track of. This review presents an overview over the available methods and their weaknesses and strength. The first use of PVE was in patients with large hepatocellular carcinomas and then translated to bilobar liver metastases. The increase of liver volume induced by PVE equals that of portal vein ligation, but both result only in a moderate volume increase. While awaiting sufficient liver growth, 20-40% of patients fail to achieve resection, mostly due to progression of disease. The MD Anderson Cancer Center group improved the PVE methodology by adding segment 4 embolization (“high-quality PVE”) and demonstrated that oncological results were better than non-surgical approaches in this previously unresectable patient population. In 2012, a novel method of liver regeneration was proposed and called Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS). ALPPS accelerated liver regeneration by a factor of 2-3 and increased the resection rate to 95-100%. However, ALPPS fell short of expectations due to a high mortality and a limited utility only in highly selected patients. Accelerated liver regeneration, however, was there to stay. This is evident in the multiplicity of ALPPS modifications like radiofrequency- or partial-ALPPS. Overall, rapid liver regeneration allowed an expansion of resectability with increased perioperative risk. A standardized low risk approach to rapid hypertrophy has been missing and the techniques used depend on local expertise and preference. Recently, however, simultaneous portal and hepatic vein embolization (PVE/HVE), appears to offer both, rapid hypertrophy and no increased clinical risk. While oncological results remain unknown, PVE/HVE has the potential to become the future gold standard.